Triphenylacrylonitrile decorated N-phenylcarbazole: Isomeric effect on photophysical properties. (July 2018) - Pei, Supeng; Chen, Xiaohong; Zhou, Zongshang; Zou, Hanzeng; Gong, Yongyang
Abstract: Efficient solid-state emitters show promising applications in optical, biological and optoelectronic areas. Understanding the structure-property relationships is essential to explore their applications. In this contribution, several isomers of triphenylacrylonitrile (TPAN) decorated N-phenylcarbazole (PCZ) were synthesized and their photophysical properties were investigated. The substitution position exerts a distinct influence on the photophysical properties, including absorption, emission and mechanochromism. All luminogens demonstrate aggregation-enhanced emission (AEE) characteristics with efficiency up to 56.80%. Except o -TPANPCZ, other isomers show distinct reversible luminescent mechanochromism, owing to the destruction and restoration of their twisted conformations and intermolecular interactions in the crystalline and amorphous states. Highlights: The combination of PCZ and TPAN can generate new AIE-active mechanochromic luminogens. These AIE-active luminogens are owed to the CIE property of TPAN, twisting conformations and intramolecular interactions. All luminogens demonstrate aggregation-enhanced emission (AEE) characteristics with efficiency up to 56.80%. Except o -TPANPCZ, other isomers show distinct reversible luminescent mechanochromism.